The Limits of the Declaratory Judgment - Malcolm Rowe, Justice; Shnier, Diane (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2022)
A declaratory judgment is a determination of rights without consequential relief. Declaratory judgments can be highly useful for litigants, but they are also somewhat lacking in doctrinal clarity, raising a number of questions that go to the core of the judicial role. What does it mean to have a legal right, or to declare the existence of a legal right, if that right, while recognized, is not enforced? It has been held that a declaratory judgment is available only when there is a real dispute between the parties, but what is a real legal dispute without legal rights that can be enforced? When is it the business of courts to declare the existence of such a right?The purpose of this article is to provide an overview of the use of the declaratory judgment. This article identifies significant outstanding issues, but suggests no resolution. It begins by setting out the history of the declaratory judgment in England and in Canada and traces traditional judicial reluctance to recognize a right without a remedy. It then explores the character of declaratory relief, its similarity with other areas of law, and the tension inherent in declaring rights without a remedy. In the second half of this article, this tension is illustrated through a discussion of recent Canadian cases, mainly at the appellate level, on five topics: declarations about contracts, Aboriginal treaties, statutes, administrative action, and constitutional rights.